Reprocessing and reuse of single-use medical devices: perceptions and concerns of relevant stakeholders toward current practices. Issue 1 (March 2019) - Grantcharov, Peter; Ahmed, Shushmita; Wac, Katarzyna; Rivas, Homero
ABSTRACT: Background: Research and history have largely shown the covert billion-dollar global market of single-use medical device (SUD) reprocessing and reuse to be a safe endeavor, but awareness and perceptions of the practice both within and outside of healthcare have received limited attention. Methods: Responses for patients, physicians, and medical practitioners were attained on both online and article-based surveys, in which attitudes and perceptions of SUD reprocessing and reuse were expressed in an assortment of closed-ended questions and partially closed-ended questions. Results: Of the 214 participants, a collective 77% were unaware that the Food and Drug Administration allows SUD reprocessing and reuse. This included 65% of physicians and 84% of patients, which were significantly different proportions ( P = 0.005). A significantly greater proportion of patients than physicians (92 vs. 68%) also felt that hospitals bear the responsibility of informing patients of the practice as part of their care ( P < 0.001). Conclusion: There is a profound lack of awareness of SUD reprocessing and reuse among all relevant stakeholders. In addition, the overwhelming desire for transparency among patients further forces the debate of whether current, covert methods should be altered, in addition to the question of who bears this responsibility. Despite research and history having shown the practice to be safe, apprehension and misconceptions remain. Survey results suggest that education may be able to subdue such patient concerns. What is known about the topic? The efficacy and safety of SUD reprocessing and reuse. The prevalence of SUD reprocessing and reuse. The economic and environmental benefits of SUD reprocessing and reuse. What does this article add? Significant insight into patient perception of SUD reprocessing and reuse, and consequent discussion of the ethics relating to this practice. Insight into the discrepancy of perceptions between healthcare professionals performing the SUD reprocessing and reuse, perceptions of the patients that these products are being used on, and reality. A comprehensive review of current safety record data and prevalence of this practice.